Physiological parameters in neonatal lambs of the Bergamasca breed - Ulian, Carla Maria Vela [UNESP]; Koether, Karoline [UNESP]; Lourenço, Maria Lucia Gomes [UNESP]; De Souza Gonçalves, Renato [UNESP]; Sudano, Mateus José; Da Cruz, Raíssa Karolliny Salgueiro [UNESP]; Da Silva, Naiana Branchini [UNESP]; Chiacchio, Simone Biagio [UNESP] (My University, 2014)
Background: The management of newborn lambs from birth until weaning has an impact on herd productivity, i.e., the economic return will depend on the survival of the offspring. Physiological parameters must be carefully analysed according to the age of the animal to establish a diagnosis and treatment plan. Therefore, the aim of this study was to monitor the physiological parameters (temperature, body weight, heart rate and respiration) between birth and 15 days of age, and between 24 h and 35 days to validate such parameters during these critical periods and for neonatal adaption in sheep Materials, Methods & Results: Two studies were carried out to analyse the physiological parameters of rectal temperature (°C), body weight (BW), heart rate (HR) and respiratory rate (RR) in male and female lambs of the Bergamasca breed maintained under identical conditions of management (intensive farming system). The first study used lambs (n = 29) from birth up to 15 days of age evaluated immediately after birth and at 24, 48, 72, 7 and 15 days of age. In the second study, lambs (n = 22) were evaluated at 1 day of age and then weekly at 7, 14, 21, 28 and 35 days of age. Linear models for repeated measures were used to compare the averages of each variable-response between the times studied. Tukey's method was used to adjust the resulting P-values of multiple comparisons between time-points. The level of statistical significance for the first and second study was 1[%] (P < 0.01) and 5[%] (P < 0.05), respectively. There were no significant differences in respiratory rate with increasing age in either of the two studies (P < 0.01; P < 0.05). In both studies, there was a positive correlation between variations in rectal temperature (average: 39.1 ± 0.58°C; P < 0.01 and 39.5 ± 0.28°C; P < 0.05) and significant decreases in heart rate (159.4 ± 15.6 bpm, P < 0.01 and 167.5 ± 12.89 bpm, P < 0.05). In the first study, the weights of the lambs progressively increased from birth to 15 days of age, with an average daily body weight (BDW) of 0.338 ± 0.09 kg (P < 0.01). In the second study, which was conducted over a 35 day period, the BDW was 0.213 ± 0.07 kg starting from 1 day of age (P < 0.05). The average values for respiratory and heart rates were higher for newborn lambs compared to the corresponding values for adults. Discussion: In newborn lambs, thermoregulatory mechanisms are not yet fully developed until the first week of life, which can lead to an increase in rectal temperature. In this age group, a slight increase in rectal temperature is not indicative of caloric stress, except if it is accompanied by increases in respiratory and cardiac frequencies, which were not observed in this study. The respiratory rate values found in this study were inconsistent compared to those found in the literature; furthermore, these values were higher than those reported for adult lambs, possibly owing to differences in species, room temperature and location of calving between this and past studies. For the most part, the HR values are higher than those observed for adult lambs, which can result in a misdiagnosis when the reference values for adults are used. The lambs in this study presented similar weights to those reported in the literature for the same species but less than the average weight reported for mestizos Bergamasca x Ile de France, suggesting that the hybrid vigour benefits weight gain. Due to differences in breed, gender and location, it is not possible to establish a single physiological pattern. Therefore, more comprehensive studies that assess various production systems and species and their impact on the physiology of newborns are needed.